Game-based Activity Method: A Case of Grade 5 Students - Hanna, H.; Abdul, Sofia L.; Cruz, Angel Dianne B. Dela; Manalo, Zyji T.; Papna, Fiona Marie L.; Falle, Jayson A. (Indonesian Journal of Teaching in Science, 2021)
The main purpose of this research is to further address this gap with pupils to understand further game-based learning. The study was conducted at Tacurong City, Sultan Kudarat. Five students (grade 5) of Tacurong Pilot Elementary School were selected purposively and considered their availability. The researchers used semi-structured questionnaires via an online one-on-one interview with the participants through Google Meet. This was to find out that the game-based activity method makes them more interested in learning and it becomes easier for them generally to answer their homework and activities using the game-based method. It is disclosed that the use of games to show educational content inevitably raises the question of their compatibility with deep learning. Despite their disadvantages, games have a series of undeniable positive features: using one and also the same game to develop several skills in students at once; providing visual, life-like examples for practical situations; forcing all learners to undertake learning, discovery, thinking, thus enhancing self-esteem and self-improvement.